Low-temperature phase segregation in La2/3Ba1/3MnO3: Manifestation of nonequilibrium thermodynamics - Beznosov, A.B.; Fertman, E.L.; Desnenko, V.A.; Feher, A.; Kajnaková, M.; Ritter, C.; Khalyavin, D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Thermodynamic characteristics of the perovskite-like compound La2/3Ba1/3MnO3 exhibiting structural phase transformation of the martensitic type with characteristic temperature Ts ≈ 200 K have been studied in the temperature range 2–340 K. Step-like hysteretic temperature behavior of the effective heat capacity has been revealed at 150–250 K and attributed to the discrete kinetics and a latent heat of the martensitic transformation. Magnetic subsystem was found exhibiting magnetic glass state below 220 K and temperature hysteresis of the magnetic susceptibility brightly pronounced in the 40–100 K and 180–230 K regions. The Debye and Einstein temperatures, qD = 230 K and qE = 500 K, respectively, derived from the experimental Debye–Waller factors for La/Ba, Mn and O sublattices, have been used to refine contributions from the structural and magnetic transformations to the heat capacity and to reveal thermodynamically nonequilibrium states.